A cross-sectional study of factors associated with uptake of vaccination against influenza among older residents in the postpandemic season in Beijing, China - Zheng, Yang (BMJ Publishing Group, 2013)
OBJECTIVE: Annually, influenza epidemics are associated with high mortality rates, notably among elderly persons. The aim of the study was to examine the level of influenza vaccine coverage among Chinese residents aged 60 years and older and to examine the demographic, behavioural and lifestyle health factors associated with vaccine receipt. DESIGN: Cross-sectional study. SETTING: Beijing, China. PARTICIPANTS: Stratified sampling was used to recruit participants for this study. A total of 2578 people aged 60 years and older consented to participate in this study. Questionnaires from 2481 participants were valid and were included in the final analysis. OUTCOME MEASURES: Influenza vaccination status and factors associated with vaccination. METHODS: In late 2010, a survey was conducted with residents from three urban and three rural districts in Beijing, China. Multivariate logistic regression was performed to detect the factors associated with influenza vaccination. RESULTS: 2481 older people (aged ≥60 years) were included in the final analysis. In 2010, 44% had received the annual influenza vaccine. Lower education level, poor health status of the participant, regular taking exercises and considering that vaccine is the best measure for preventing influenza were associated with influenza vaccination coverage. CONCLUSIONS: Influenza vaccine coverage in Beijing still remains suboptimal. Further work needs to be undertaken to ascertain whether the methods used to distribute the vaccine are adequate and whether health professionals are appropriately promoting the vaccine.